Differentiating medulloblastoma in adults - Ammar, A.; Al-Majid, H.; Anim, J.T.; Kutty, M.K.; Ibrahim, A.W. (Neurological Research, 1991)
We present two cases of medulloblastoma in adult patients showing extensive astrocytic differentiation. In one case, there was synchronous oligodendroglial differentiation, both changes appearing after treatment with radiotherapy. The possible role of radiotherapy in the differentiation is discussed.
Keywords: Adult; Astrocytoma/*pathology; Brain Neoplasms/*pathology/radiography/therapy; Cell Transformation, Neoplastic; Combined Modality Therapy; Humans; Male; Medulloblastoma/*pathology/radiography/therapy; Neoplasm Recurrence, Local/etiology/*pathology/radiography; Oligodendroglioma/*pathology; Tomography, X-Ray Computed